Electrochemical C–H functionalization to synthesize 3-hydroxyalkylquinoxalin-2(1H)-ones via quinoxalin-2(1H)-ones and aldehydes. Issue 21 (26th September 2022) - Liu, Han-Fu; He, Mu-Xue; Tang, Hai-Tao
Abstract : We reported an electrocatalytic direct C3-hydroxyalkylation of quinoxalin-2(1 H )-ones to construct 3-hydroxyalkylquinoxalin-2(1 H )-one derivatives, which uses unprotected quinoxalin-2(1 H )-ones and aliphatic aldehydes as substrates. Abstract : Direct C3-functionalization of quinoxalin-2(1 H )-ones is a convenient way to develop new and sustainable strategies, which are important for natural product and drug modification. Herein, we report an electrocatalytic C–H activation method, which synthesized 3-hydroxyalkylquinoxalin-2(1 H )-ones via a radical pathway using unprotected quinoxalin-2(1 H )-ones and aliphatic aldehydes as the substrates. This electrolysis strategy avoids the use of stoichiometric oxidants and heavy metal catalysts. Further scale-up studies in electrochemical continuous flow reactors have demonstrated the potential application value.